Virtual Reality in Engineering Education: A Virtual Introduction to Unit Operations and Process Scaling - Robles, Laura Eugenia Romero; Ek, Jackeline Iturbe (World Engineering Education Forum - Global Engineering Deans Council (Online), 2023)
Over the past few decades, digital technologies have completely transformed the world around us. There are studies that claim that the next great digital transformation of the way we live, communicate, work, trade and learn will be driven by technologies such as Virtual Reality (VR), Augmented Reality (AR) and Artificial Intelligence (AI), among others [1]. Virtual reality (VR) technology has evolved dramatically over the years as its applications have grown. The interest in students is due to the immersive experience and the feeling of presence, of being transported into the virtual environment and losing connection with the physical world. The increasingly frequent use by our students of technological devices and applications in their daily lives, also makes daily the use of technology for students to test, reinforce and practice the theoretical knowledge acquired in the classroom. This paper presents the students' perception of their learning by performing a virtual reality activity of the course Prototyping. The paper presents the impact on students' perception of the stimulus of a virtual digital activity on their learning. The results of this work show that students value the activity, demonstrating an increased understanding of the subject topics in addition to showing a high level of engagement in the subject compared to traditional learning environments.